2009 15th IEEE Pacific Rim International Symposium on Dependable Computing 2009
DOI: 10.1109/prdc.2009.66
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Irrecoverable Read Errors on Disk Array Reliability

Abstract: Abstract-We investigate the impact of irrecoverable read errors-also known as bad blocks-on the MTTDL of mirrored disks, RAID level 5 arrays and RAID level 6 arrays. Our study is based on the data collected by Bairavasundaram et al. from a population of 1.53 million disks over a period of 32 months. Our study indicates that irrecoverable read errors can reduce the mean time to data loss (MTTDL) of the three arrays by up to 99 percent, effectively canceling most of the benefits of fast disk repairs. It also sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…They express reliability as the mean-time-to-data loss (MTTDL) for D+1 and D+2 configurations [Dholakia et al 2006;EMC 2007;Gao et al 2010;Oracle 2010;Paris et al 2009; Serve The Home 2011], the number of data loss events over time [Elerath and Pecht 2009;Rao et al 2006], or use a normalized magnitude of data loss as a replacement for MTTDL.…”
Section: Previous Workmentioning
confidence: 99%
“…They express reliability as the mean-time-to-data loss (MTTDL) for D+1 and D+2 configurations [Dholakia et al 2006;EMC 2007;Gao et al 2010;Oracle 2010;Paris et al 2009; Serve The Home 2011], the number of data loss events over time [Elerath and Pecht 2009;Rao et al 2006], or use a normalized magnitude of data loss as a replacement for MTTDL.…”
Section: Previous Workmentioning
confidence: 99%
“…In addition, clean drives will develop sector failures at rate λ , and we scrub the drives to remove the sector errors at rate µ . This model was studied in [5], and the approach here is similar but generalized to an arbitrary number of check drives. Figure 7 depicts the Markov chain for the M = 2 cases, and Table 1 gives the transition rates between states in the general case.…”
Section: Model 5: Sector Errorsmentioning
confidence: 99%
“…However this graph shows that the consideration of sector errors yields an estimate of PDL 5 that is several orders of magnitude higher than the model proposed in Section 4. [5] discusses extensively the benefits of shorter scrubbing intervals (increased µ ), finding that more frequent scrubbing can substantially increase the MTTDL of the system and thus make it more reliable. We find that scrubbing more frequently can indeed increase the reliability of the system, but the effect is much less dramatic than adding another check drive.…”
Section: Transitionmentioning
confidence: 99%
“…investigated a RAID level 6 array with six disks and concluded that scheduling scrubbing scans once a month instead of once a year can increase the MTTDL of the array from 600 to almost 1,000 percent depending on the disk repair time [15].…”
Section: Data Lossmentioning
confidence: 99%